Employment of Vehicle-to-Grid Technology to Decrease the Economic-Environmental Costs Equipped with a Mixed-Integer Non-Linear Programming Approach - Jinkui Li; Huahui Li (Advances in Engineering and Intelligence Systems)
In the present work, the programming of thermal production units is achieved using vehicle-to-grid (V2G) technology. The proposed solution is developed through the mixed-integer non-linear programming (MINLP) method in the GAMS simulation environment. The main objective of this study is to minimize the considered objective function (OF). Several constraints are also considered in this optimization problem, which should be met by the proposed method. The proposed method is evaluated to validate its efficiency. This technique is tested on an IEEE 10-unit case study that includes 5000 EVs (electric vehicles). According to the obtained results, the utilized V2G can significantly influence the unit commitment (UC) problem. EVs introduce new loads to the electrical network, which increases the expenditure on power production. Nevertheless, the coordinated charging method and rational utilization of V2G power can reduce this expenditure. Additionally, minimizing operating expenses as the programming goal presents a better overall economic and environmental performance in thermal units with V2G cases.